Soil Fungal Community Responses to the Silver Nanoparticles Contamination as Assessed by Illumina Next Generation Sequencing (NGS) - Oktarina, Hartati; Singleton, Ian (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2020)
The increasing use of silver nanoparticles (AgNPs) due to its excellent antimicrobial activity in commercial products prompting concerns about their fate in the environment. The toxicity of AgNPs is mainly the result of Ag+ ions. In this study, soil was experimentally contaminated with 100 mg kg-1 of AgNO3 to investigate its effect on fungal soil community. Deoxyribonucleic acid (DNA) from the soil was extracted at the 6th, 12th, and 24th month of observation and assessed by Illumina Next Generation Sequencing (NGS). The results show that, the pollutant change fungal community in soil. After 12 months incubated the number of fungal species in the soil reduced significantly and 40% of the community was dominated by one species.